2013
DOI: 10.1007/s00227-013-2334-1
|View full text |Cite
|
Sign up to set email alerts
|

Surfacing behavior and gas release of the physostome sprat (Sprattus sprattus) in ice-free and ice-covered waters

Abstract: Upward-facing echosounders that provided continuous, long-term measurements were applied to address the surfacing behavior and gas release of the physostome sprat (Sprattus sprattus) throughout an entire winter in a 150-m-deep Norwegian fjord. During ice-free conditions, the sprat surfaced and released gas bubbles at night with an estimated surfacing rate of 3.5 times per fish day−1. The vertical swimming speeds during surfacing were considerably higher (~10 times) than during diel vertical migrations, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…In contrast to summer, water column fish density in the winter was higher and much less variable. The majority of fish in the passage at that time was likely to be herring, whose presence was supported by frequent trails of bubbles seen rising from schools or individuals in the echogram (herring and other clupeids are known to release swim bladder gas through the anal duct [23,24]). Rainbow smelt and sticklebacks were also potentially present in the area based on what is generally known of their life histories [21], and acoustically tagged striped bass have been recorded repeatedly passing through Minas Passage in the winter [3].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to summer, water column fish density in the winter was higher and much less variable. The majority of fish in the passage at that time was likely to be herring, whose presence was supported by frequent trails of bubbles seen rising from schools or individuals in the echogram (herring and other clupeids are known to release swim bladder gas through the anal duct [23,24]). Rainbow smelt and sticklebacks were also potentially present in the area based on what is generally known of their life histories [21], and acoustically tagged striped bass have been recorded repeatedly passing through Minas Passage in the winter [3].…”
Section: Discussionmentioning
confidence: 99%
“…These fish lack gas secreting glands for adjustment of the swimbladder at different depths, so the swimbladder becomes successively compressed at increasing depth making the fish negatively buoyant in deeper water (Solberg & Kaartvedt 2014). Using bottom mounted, upward facing echosounders during wintertime in Bunnefjorden, Norway, Kaartvedt et al (2009) tracked individual sprat and showed that the fish continuously swam up and down at depths > 55 m, and this way maintained the same depth over time.…”
Section: Feeding and Vertical Distribution Dynamics Of Spratmentioning
confidence: 99%
“…In the present study, the ascent of sprat from depths of 55 to 60 m at dusk when predation risk is reduced may therefore also be due to a strategy of minimizing swimming costs by reducing negative buoyancy. Secondly, Kaartvedt et al (2009), Solberg & Kaartvedt (2014 and Solberg et al (2015) tracked individual sprat performing short excursions to the surface at night and ascribed this swimming behaviour to refilling the swimbladder by gulping atmo spheric air. However, even in situations of inverse DVM, with sprat aggregating in deep water at night, surfacing did not seem to impact the vertical distribution pattern at large (Solberg & Kaartvedt 2014).…”
Section: Feeding and Vertical Distribution Dynamics Of Spratmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to locomotion through body-muscle contraction, bull trout may also use their swim bladder to change swimming depth. In fishes, the swim bladder is airfilled sac located in the coelomic cavity below the vertebral column (Holbrook and Perera 2011 (Mehner 2012;Solberg and Kaartvedt 2014), it remains feasible that both swimming and swimbladder regulation are operational modes of bull trout motion capacity.…”
Section: Motion Capacitymentioning
confidence: 99%